Interesting life father’s of Polish Ophthalmology – Wiktor Feliks Szokalski (1811–1891) – In 200 years anniversary of his birth - Grzybowski, Andrzej; Winiarczyk, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica, 2011)
Victor Szokalski is considered to be the father of Polish ophthalmology. He was born in Warsaw in 1811, where he also began his medical studies. He fought in the November’s Uprising. He was awarded the Military Cross Virtuti. After its fall he went to Germany, where he continued his studies. In 1834 he defended his doctoral thesis. Then he moved to France, where worked at the Eye Clinic of Jules Sichel. He wrote many articles for medical journals and taught students. Already in Paris he acted in a number of social societies, collaborated with Prince Adam Czartoryski, was a friend of Adam Mickiewicz. Fifteen years later he returned to Warsaw, where became a consultant, then the chief at the Ophthalmic Institute . For 33 years he has served as secretary of the Warsaw Medical Society. He wrote the first Polish original textbook of ophthalmology. He died in Warsaw in 1891.